MORPHOLOGICAL AND GENETIC DIVERSITY OF KAZAKH HORSE BREEDS: FUNDAMENTALS FOR SELECTION AND CONSERVATION OF BIOLOGICAL RESOURCES - Beishova, I. S.; Shamshidin, A. S.; Muhatai Geminggul, I.; Kuzhebayeva, U. Zh.; Bekova, G. S.; Salimova, D. K. (ЗКАТУ им. Жангир хана, 2025)
The study is dedicated to the study of domestic horse breeds of Kazakhstan (Kushum, Mugalzhar, Adai, Jabe) in order to identify their morphological and genetic characteristics to improve breeding programs. The paper presents the results of the bonitation work, including the analysis of body weight, measurements (height at the withers, chest circumference, oblique body length) and age and gender characteristics. It has been established that the Kushum breed shows the biggest mass (stallions - up to 650 kg, mares - up to 530 kg) and pronounced sexual dimorphism, while the Mugalzhar breed is characterized by uniformity of measurements (height at the withers – 147-148 cm) and high meat productivity. The Adai and Jabe breeds are compact in size (140-144 cm at the withers) and adaptable to harsh conditions. The methodology included the collection of biological material and data from farms in Kazakhstan, as well as preparation for genome-wide sequencing to analyze genetic variations. The results showed that the selected individuals (Jabe, Mugalzhar, and Adai stallions) have the best phenotypic characteristics, which makes them valuable for preserving genetic diversity. The conclusions emphasize the importance of studying local breeds for the development of meat and dairy horse breeding in Kazakhstan. The data obtained opens up prospects for breeding aimed at enhancing productive qualities and resilience to environmental challenges. The work contributes to the conservation of unique genetic resources and the optimization of breeding programs.
Morphological and genetic diversity of kazakh horse breeds: fundamentals for selection and conservation of biological resources / I. S. Beishova, A. S. Shamshidin, I. Muhatai Geminggul, U. Zh. Kuzhebayeva, G. S. Bekova, D. K. Salimova. - Текст : непосредственный // "Ғылым, зерттеулер, білім: даму тенденциялары" атты XXV халықаралық ғылыми-практ. конф. жинағы = Сollected papers XXV International scientific and practical conference "Science, research, education: development trends"= «Наука, исследования, образование: тенденции развития»: cб. XXV междунар. науч.-практ. конф. - Орал: Жәңгір хан атындағы БҚАТУ. - 2025. - Р. 112-121 (Uralsk).
Keywords: horse breeding; horse breeds; live weight; measurements; genetic diversity; Kazakhstan; зкату; отечественное издание